2014
DOI: 10.1017/s1478951514000595
|View full text |Cite
|
Sign up to set email alerts
|

Family evaluation of hospice care: Examining direct and indirect associations with overall satisfaction and caregiver confidence

Abstract: These findings help to (1) pinpoint those most at risk for being less satisfied with hospice, (2) identify which aspects of care may be most strongly related to overall outcomes, and (3) provide a model for examining complex associations among FEHC variables that may be employed by other researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…In both heart failure and cancer, caregivers' perception of patient symptoms was associated with satisfaction across multiple subdomains. This finding is similar to that of Holland et al, 15 who found that patients with more complex symptom profiles were less likely to be satisfied. However, reported patient dyspnea was associated with global and symptom management only in the heart failure cohort.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In both heart failure and cancer, caregivers' perception of patient symptoms was associated with satisfaction across multiple subdomains. This finding is similar to that of Holland et al, 15 who found that patients with more complex symptom profiles were less likely to be satisfied. However, reported patient dyspnea was associated with global and symptom management only in the heart failure cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found that caregivers of black or racial minority (nonwhite) patients are less likely to be satisfied globally and with symptom management; and that these differences persist even in hospices with a higher proportion of black care recipients. 15,20,21 In two studies by Rhodes et al, 12 the analysis included adjustment for diagnosis, but did not examine whether the effect of race differed by diagnosis. In addition to differences in global and symptom management satisfaction, Holland et al 15 also found that caregiver of racial minority (nonwhite) patients were less likely to be satisfied with the teaching and emotional support provided by the hospice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is decent access to equipment in the home to address physical needs, but some barriers exist to accessing pain management medications readily (e.g., provincial drug coverage policies, access to physician to write prescriptions, and lack of access to prescriptions after-hours or delivery). 36,39,40 Holistic management of nonphysical and physical symptoms…”
Section: Pain and Symptom Managementmentioning
confidence: 99%
“…Most patients receive hospice services at home. Family satisfaction with hospice care is very high, 2 and nationally, almost half of the patients who die each year have hospice support. 3 Unfortunately, referral to hospice is usually late in the course of the disease, and although care could be provided for longer periods, the median length of stay after hospice enrollment is less than three weeks, and approximately 35% of those who obtain hospice services die within a week.…”
Section: Introductionmentioning
confidence: 99%